BCD ADDER ENTERPRISE EXHAUSTING NOVEL REVERSIBLE LOGIC FOR STUMPY POWER APPLICATIONS - Reddy, K. Niranjan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reversible logic has garnered tremendous attention in the recent years owing to its capacity to lower the power dissipation which is the major criterion in low power digital design. It finds use in many fields, including nanotechnology, biotechnology, quantum computing, optical information processing, DNA computing, and advanced computing. This work introduces a novel reversible gate and uses it to create an improved reversible BCD adder. The suggested architecture is shown to be more efficient than current ones in terms of gate count, garbage output count, and quantum cost, according to a comparison result.